Insecticidal Activity of [Cu(H2NTA)2].2H2O in Aedes aegypti Larvae (Diptera: Culicidae) - Lima, Alessandra Ramos; de Arruda, Eduardo José; de Carvalho, Cláudio Teodoro; da Silva, Cícera Maria; Fernandes, Magda Freitas; Kato, Mika Fumie Haiashi; Cabrini, Isaías; Andrade, Carlos Fernando S. (Orbital: The Electronic Journal of Chemistry, 2015)
The demand for new insecticides and alternative strategies for the population control of Aedes aegypti has stimulated research to obtain new compounds with broad biological activity. Accordingly, the dihydrogen nitrilotriacetate complex of copper (II) dihydrate, [Cu(H2NTA)2].2H2O, was synthesized by the stoichiometric reaction of nitrilotriacetic acid (H3NTA) hydroxide with basic copper carbonate (II) (Cu2(OH)2CO3) and characterized by the spectroscopic techniques UV-Vis and FT-IR. The biological toxicity in A. aegypti was determined by bioassay using concentrations ranging from 90.0 mg L−1 to 897.4 mg L−1. The LC50 obtained was 146.11 mg L−1 [132.18–160.10] and the LT50 obtained at a concentration of 897.4 mg L−1 was 70.61 min [38.21–94.90]. The results showed that the complex obtained in this work is a potential metal-insecticide.DOI: http://dx.doi.org/10.17807/orbital.v7i4.735